Sentinel Lymph Node Mapping in Endometrial Cancer: A Comprehensive Review - Zhai, Lirong; Zhang, Xiwen; Cui, Manhua; Wang, Jianliu (Frontiers in Oncology, 2021)
Endometrial cancer (EC) is known as a common gynecological malignancy. The incidence rate is on the increase annually. Lymph node status plays a crucial role in evaluating the prognosis and selecting adjuvant therapy. Currently, the patients with high-risk (not comply with any of the following: (1) well-differentiated or moderately differentiated, pathological grade G1 or G2; (2) myometrial invasion< 1/2; (3) tumor diameter < 2 cm are commonly recommended for a systematic lymphadenectomy (LAD). However, conventional LAD shows high complication incidence and uncertain survival benefits. Sentinel lymph node (SLN) refers to the first lymph node that is passed by the lymphatic metastasis of the primary malignant tumor through the regional lymphatic drainage pathway and can indicate the involvement of lymph nodes across the drainage area. Mounting evidence has demonstrated a high detection rate (DR), sensitivity, and negative predictive value (NPV) in patients with early-stage lower risk EC using sentinel lymph node mapping (SLNM) with pathologic ultra-staging. Meanwhile, SLNM did not compromise the patient’s progression-free survival (PFS) and overall survival (OS) with low operative complications. However, the application of SLNM in early-stage high-risk EC patients remains controversial. As revealed by the recent studies, SLNM may also be feasible, effective, and safe in high-risk patients. This review aims at making a systematic description of the progress made in the application of SLNM in the treatment of EC and the relevant controversies, including the application of SLNM in high-risk patients.